(untitled) (Scientific journal of the Fergana State University, 2026)
The article substantiates the necessity of deepening the theoretical foundations and practical content of physical education for preschool children, as well as equipping educators with specialized competencies in the field of physical culture. The proposals developed by the author highlight the need to create an “advanced state program in physical education” and to conduct the approbation of its educational materials. The research results provide a practical basis for developing physical culture in the preschool education system, promoting a healthy lifestyle, and enhancing the professional training of educators.